2008
DOI: 10.1002/cne.21641
|View full text |Cite
|
Sign up to set email alerts
|

Brain distribution and evidence for both central and neurohormonal actions of cocaine‐ and amphetamine‐regulated transcript peptide in Xenopus laevis

Abstract: We tested the hypothesis that, in the amphibian Xenopus laevis, cocaine- and amphetamine-regulated transcript peptide (CARTp) not only has widespread actions in the brain but also acts as a local factor in endocrine pituitary cells and/or is neurohemally secreted into the circulation to control peripheral targets. CARTp-immunoreactive cells occur in the olfactory bulb, nucleus accumbens, amygdala, septum, striatum, nucleus of Bellonci, ventrolateral nucleus, central thalamic nucleus, preoptic nuclei, and supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 54 publications
5
27
0
Order By: Relevance
“…CARTp is synthesized as a precursor with several potential cleavage sites, and studies in mammals have shown that several smaller active peptides are generated by prohormone convertases (Dey et al, ; Stein et al, ). Our results are similar to what has been shown in amphibians (Lázár et al, ; Roubos et al, ) and teleost fish (Singru et al, ), in which antibodies against CARTp recognize a band just below 14 kDa. Thus it is possible that in birds, and other vertebrates, antibodies raised against mammalian CART peptide only recognize a portion that is later cut in the processing of the peptide.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…CARTp is synthesized as a precursor with several potential cleavage sites, and studies in mammals have shown that several smaller active peptides are generated by prohormone convertases (Dey et al, ; Stein et al, ). Our results are similar to what has been shown in amphibians (Lázár et al, ; Roubos et al, ) and teleost fish (Singru et al, ), in which antibodies against CARTp recognize a band just below 14 kDa. Thus it is possible that in birds, and other vertebrates, antibodies raised against mammalian CART peptide only recognize a portion that is later cut in the processing of the peptide.…”
Section: Discussionsupporting
confidence: 92%
“…Western blot analysis showed an intense band around 16 kDa and a smaller band around 14 kDa for the pigeon. While the expected size for functional fragments of CARTp is around 5 kDa (Cai et al, ), bands at higher molecular weight are consistent with what has been found in other vertebrates (see Discussion; Lázár et al, ; Roubos et al, ). The antibody used was raised against the rat CART peptide, which shows a high degree of identity with the chicken and budgerigar ( Melopsittacus undulates ) putative signal peptides, differing in only three amino acids (98% matching; Cai et al, ).…”
Section: Resultssupporting
confidence: 85%
“…Immunocytochemistry has revealed a large “bouquet” of neurochemical messengers in Xenopus MCN perikarya and in neurohemal axon terminals in both the median eminence and the pituitary pars nervosa (Van Wijk and Roubos, 2009; Van Wijk et al, 2010). In addition to mesotocin, vasotocin, and corticotropin-releasing factor (CRF), these messengers include thyrotropin-releasing hormone (TRH; Verburg-Van Kemenade et al, 1987c; Tonosaki et al, 2004), BDNF (Wang et al, 2004, 2005; Calle et al, 2006c), metenkephalin (Van Wijk et al, 2010), Ucn1 (Calle et al, 2005), pituitary adenylyl cyclase-activating polypeptide (PACAP; Kidane et al, 2007a, 2008) and cocaine- and amphetamine-regulated transcript peptide (CART; Roubos et al, 2008). Except for CART, all these factors can stimulate the secretion of αMSH from melanotrope cells in vitro .…”
Section: The Melanotrope Neuroendocrine Transducer Cells Of the Southmentioning
confidence: 99%
“…This peptide is involved in the development of anxiogenic reactions during narcotic use [5] and formation of narcotic addition [11,13]. It modifies neuroendocrine relationships determining the regulation of alimentary and sexual behavior and the mechanisms of energy homeostasis [8][9][10]12,15].…”
mentioning
confidence: 99%
“…This peptide is involved in the development of anxiogenic reactions during narcotic use [5] and formation of narcotic addition [11,13]. It modifies neuroendocrine relationships determining the regulation of alimentary and sexual behavior and the mechanisms of energy homeostasis [8][9][10]12,15].Paleoamygdala is a neuroendocrine center of the brain playing an important role in the organization of alimentary, sexual, aggressive, and defense behavior [3,4]. It should be noted that shifts in these behavioral forms are characteristic of clinical picture of drug abuse.…”
mentioning
confidence: 99%